Brain-derived neurotrophic factor as predictor of early-onset poststroke depression - Uslu, Emine Yildirim; Yildiz, Sevler; Korkmaz, Sevda (Sage Publications Inc, 2026)
Background Poststroke depression (PSD) with an approximately one third prevalence in stroke patients is associated with increased morbidity and mortality. This study aimed to investigate the potential relationship between brain-derived neurotrophic factor (BDNF) levels in serum and early-onset PSD as well as clinical variables.Methods Clinical data and radiological images of 88 patients diagnosed with acute ischemic stroke were examined. Serum BDNF levels were measured within the first 72 hours following stroke diagnosis. On the 14th day following stroke diagnosis, Montreal Cognitive Assessment (MoCA), Hamilton Depression Rating Scale (HAM-D17), and National Institutes of Health Stroke Scale (NIHSS) were applied to the patients.Results Serum BDNF levels (P = 0.022) and MoCA values (P = 0.004) of patients with early-onset PSD were significantly lower, and NIHSS values (P = 0.027) were significantly higher compared to patients without early-onset PSD. There was a significantly negative correlation between BDNF value and HAMD-17 score and lymphocytes. Receiver operating characteristic (ROC) analysis was used to investigate the extent the BDNF level could predict the occurrence of early-onset PSD and cut-off values were determined. For a BDNF cut-off value of 361.51, sensitivity and specificity values were 75% and 56.2%, respectively, which indicated that BDNF may be a useful indicator associated with early-onset PSD.Conclusion Lower serum BDNF levels are associated with early-onset PSD and may serve as a potential biomarker, although causal or predictive conclusions are limited due to the study's cross-sectional design.
Keywords: brain-derived neurotrophic factor; poststroke depression; early onset; severity of depression